Are hand biomechanics affected following radial forearm flap harvest? A systematic review and meta-analysis. Issue 1 (January 2021) - Mashrah, M.A.; Aldhohrah, T.A.; Abdelrehem Moustafa, A.; Al-Sharani, H.M.; Alrmali, A.; Wang, L.
Abstract: Donor site morbidity following radial forearm flap (RFF) harvest remains a controversial issue. The aim of this meta-analysis was to answer the question "Are the range of wrist movements (range of motion, ROM) and hand strength affected after RFF harvesting?" The PubMed, Embase, Scopus, and Cochrane Library electronic databases were systematically searched (to December 2019). Self-controlled studies evaluating hand biomechanics after RFF harvest were included. Weighted mean differences with 95% confidence intervals were calculated using the random-effects model. The outcome variables were ROM, forearm movements, grip, and pinch strengths. Thirteen studies involving a total of 335 patients were included. With the exception of grip strength and supination, which showed statistically significant reductions of about 2.40 kg and 2.86° ( P  <  0.05), all other ROM, forearm movements, and pinch strengths showed an insignificant difference when the operated hand was compared to the non-operated hand ( P  >  0.05). Regression analysis showed that the method of donor site closure and size of the donor site defect had an insignificant impact on hand biomechanics. This study confirms the lack of discernible biomechanical morbidity after RFF transfer. The minimal reduction in hand biomechanics after RFF is considered to be clinically negligible.